РОБОТИЗАЦІЯ УПРАВЛІННЯ ПРОСТОРОВИМ ПОЛОЖЕННЯМ ОБ'ЄКТІВ ПРИ ВИРОБНИЦТВІ ТА ЕКСПЛУАТАЦІЇ ЛІТАЛЬНИХ АПАРАТІВ - Сахаров, Денис Юрьевич (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2017)
The variety of manufacturing processes for industrial engineering products requires high accuracy of their manufacturing and assembling methods to be satisfied. Thus, automated manipulators or special positioning devices can be used for further improvement of assembling efficiency. For instance, the positioning algorithms with high accuracy are implemented for structural elements within the method of assembly-free concept in aircraft building.In order to find a clue solution for the problem of accurate coordinate positioning, it is necessary to determine the rotation angles and linear displacements of the object during the transition from the initial position to the final state, and to calculate the displacement values of the positioning drives based on them. From the other side, the positioning of an industrial manipulator on a physical object in real time mode requires the development of an adaptive mathematical algorithm for determining the rotation angles and linear movements of the manipulator links, thus the development of a response mechanism from which the data required for calculating the trajectory of motion can be obtained.A mathematical model of the positioning of the normal actuator robotic industrial manipulator on the complex curved surface of aircraft panels, which calculation is based on the rotation matrix with respect to a fixed point on a curved surface expressed by Euler angles instead of the classical differentiation coordinate positions of the points in time for linearization displacements handling system for small changes in the coordinates of the individual nodes of the mechanism that allows to adaptive run-conductive program execution device and will provide an opportunity to define the normal to the curved surface in real time.Based on the proposed calculation method, numerical algorithm for manipulator handling can be developed. This software will allow to calculate the necessary values of the movements of the manipulator drives, which eliminates the need for a large number of iterations in the coordinate positioning process. The described method can significantly improve the performance of assembly-free concept and docking operations in aircraft building.